Profile of Planned Happenstance of Student Skills Based on Gender, Age, Regional, and Ethnicity - Akhmad Harum (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2023)
This study aims to determine the Planned Happenstance Skill Profile of students of the Faculty of Education, the State University of Makassar based on study program, gender, region, and ethnic origin. This research uses a descriptive quantitative research type. The research subjects were 355 students spread across the Guidance and Counseling, PAUD, PGSD, PLS, Educational Technology, and Special Education study programs. The research instrument used instruments prepared by KIM etc using JASP showed that the reliability test by looking at the McDonald's value of 0.905 and Cronbach's alpha with a value of 0.907 and the validity of the analysis using a confirmatory factor analysis test, the validity test of the CMIN / DF value showed a value of 3246.919/231 with a significance of 0.01, or < 2.0 see the value of CFI: 0.955, TLI: 0.947, GFI: 0.919 and data analysis using ANOVA. The study results show that the Planned Happiness Skill of the Faculty of Education's students is in the very high category. The gender aspect indicates that there is no difference in student career planning seen from the gender variable, this is evidenced by p> 0.05. However, this is different from the aspect which shows a p-value <0.01, and a mean square of 17.114. So, based on these data it can be interpreted that there are significant differences in the aspects of student curiosity in career planning by chance seen from their gender. In September, age shows that there are no planned differences in student careers seen from various ages, this is evidenced by p> 0.05. Furthermore, on the aspect of regional origin, it shows that there is no difference in students' planned happenstance career seen from the regional origin variable as well as in the ethnic aspect, there is no difference in students' planned happenstance career. Furthermore, the results of the descriptive analysis seen from the study program aspect show that the Planned Happenstance Career Inventory of education faculty students is in the high category